Analysis of Priorities for Improving the Quality of Higher Education Services to Increase Student Satisfaction in the Economics Education Study Program, Universitas Negeri Semarang - Eka Susanti; Sholihatun Nur Jannah (Dinamika Pendidikan, 2024)
This study aims to determine the suitability of the application of the HESQUAL dimensions, determine the level of student satisfaction with service quality and determine priorities for improving service quality in the Economic Education Study Program at Semarang State University. The sample that has been determined is 110 respondents. The sampling technique is using Proportional Random Sampling. Data collection methods using questionnaires. The data analysis techniques used are: (1) Confirmatory Factor Analysis (CFA) using SmartPLS version 4; (2) Customer Satisfaction Index (CSI); (3) ImportancePerformance Analysis (IPA); (4) Potential Gain in Customer Value (PGCV) using the SPSS application. The results showed that the HESQUAL model is a fit model for measuring service quality in higher education, student satisfaction is in the Satisfied category with a satisfaction value of 73% and the priority for improving service quality is the attention of lecturers to students who have difficulty understanding the material, lecturers need to determine effective learning methods, provide quality services that can increase student confidence, administrative staff help students who have difficulties, and information on the flow of academic administration carried out online.